2009
DOI: 10.1016/j.semcancer.2008.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic functions of the p53 tumor suppressor: Regulation of energy metabolism and antioxidant defense

Abstract: The p53 tumor suppressor plays pivotal role in the organism by supervising strict compliance of individual cells to needs of the whole organisms. It has been widely accepted that p53 acts in response to stresses and abnormalities in cell physiology by mobilizing the repair processes or by removing the diseased cells through initiating the cell death programs. Recent studies, however, indicate that even under normal physiological conditions certain activities of p53 participate in homeostatic regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
129
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(135 citation statements)
references
References 129 publications
(169 reference statements)
5
129
0
1
Order By: Relevance
“…By contrast, lack of p53 in Hep3B cells manifested more apparent autophagic parameters, such as LC3 lipidation, redistribution of LC3 in cytoplasmic puncta, accumulation of autophagosomes, and depletion of p62/ SQSTM1 during reperfusion. It has been reported that p53-null cells are insensitive to metabolic stress with a higher intracellular ATP level (37). Our results provide additional evidence to support the possibility that p53 null cells are better equipped with more active autophagy to survive metabolic stress.…”
Section: Discussionsupporting
confidence: 82%
“…By contrast, lack of p53 in Hep3B cells manifested more apparent autophagic parameters, such as LC3 lipidation, redistribution of LC3 in cytoplasmic puncta, accumulation of autophagosomes, and depletion of p62/ SQSTM1 during reperfusion. It has been reported that p53-null cells are insensitive to metabolic stress with a higher intracellular ATP level (37). Our results provide additional evidence to support the possibility that p53 null cells are better equipped with more active autophagy to survive metabolic stress.…”
Section: Discussionsupporting
confidence: 82%
“…The cancer mutator phenotype was invoked to explain the large number of somatic mutations found in cancer, but mutations in the p53 caretaker gene are not expressed in all cancers nor does p53 deletion produce cancer in mice suggesting a more complicated involvement of this and other genome guardians in carcinogenesis [7,[101][102][103][104]. While numerous genetic abnormalities have been described in most human cancers, no specific mutation is reliably diagnostic for any specific type of tumor [7,17,105].…”
Section: Linking Genome Instability To Mitochondrial Dysfunctionmentioning
confidence: 99%
“…For example, impaired mitochondrial function can induce abnormalities in p53 activation, while abnormalities in p53 expression and regulation can further impair mitochondrial function [85,103,113,116,[140][141][142][143]. The function of the pRB tumor suppressor protein, which controls the cell cycle, is also sensitive to ROS production through the redox state of the cell [144].…”
Section: Mitochondrial Dysfunction and The Mutator Phenotypementioning
confidence: 99%
“…(Chumakov, 2007;Green and Kroemer, 2009;McCarthy, 2011;Olovnikov et al, 2009;Vousden and Prives, 2009;Vousden and Ryan, 2009). p53 protein is encoded by the TP53 gene (OMIM no.…”
Section: Introductionmentioning
confidence: 99%